Tensile Properties of Single Jersey and 1×1 Rib Knitted Fabrics Made from 100% Cotton and Cotton/Lycra Yarns - Dereje Berihun Sitotaw; Biruk Fentahun Adamu (Journal of Engineering)
The tensile properties such as tensile strength which is measured as breaking force in Newton (N) and elongation percent (%) at break of single jersey and 1×1 rib (knitted with full needles) knitted fabrics made from 100% cotton and cotton/Lycra yarns (5% Lycra yarn content in 95% combed cotton yarn) are investigated in this research. The sample fabrics are conditioned for 24 hours at 20±1°C temperature and 65±2% relative humidity before testing. Ten specimens (five for lengthwise and five for widthwise) have been taken from each of the two knitted structures, those made from 100% cotton and cotton/Lycra (at 95/5 percent ratio blend) yarns. According to the discussion and as found from the investigations, the tensile properties of single jersey and 1×1 rib knitted fabrics made from 100% cotton and cotton/Lycra yarns are significantly different from each other and both of the knitted fabrics have high elongation percent at break with cotton/Lycra blend yarns as compared to 100% cotton yarn. Knitted fabrics made from cotton/Lycra blended yarn have low breaking force and high elongation percent at break relative to knitted fabrics made from 100% cotton yarns.